Building Bridges with Words: Teacher Student Talk Dynamics in Young Learners English Classrooms - Jeihn N. C. Budiman; Nindy N. Ganap (English Education Postgraduate Program, Universitas Negeri Manado, 2025)
Understanding effective teaching strategies alongside student needs plays a crucial role in selecting materials that align with students preferred learning styles When teaching English to young learners age is a significant factor as early childhood is considered a critical period for language acquisition During this golden age the collaborative efforts of parents and teachers can enhance students cognitive development leading to better learning outcomes This study utilized a literature review method drawing from various previous research studies The analysis followed several steps starting from identifying the problem to interpreting the data Classroom interaction emerged as a key component of the learning process where both teachers and students are expected to actively participate The findings reveal a noticeable imbalance between teacher talk and student talk as supported by prior research This imbalance highlights an important issue that educators need to address to foster a more engaging and participatory learning environment for students < em>< p>